2011
DOI: 10.1371/journal.pone.0021839
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Related Factors among HIV-Positive Spouses from Serodiscordant Couples under Antiretroviral Therapy in Henan Province, China

Abstract: ObjectiveTo describe the quality of life and related factors in HIV-positive spouses undergoing ART from discordant couples.MethodsA cross-sectional study was conducted among 1,009 HIV-positive spouses from serodiscordant couples in Zhumadian, Henan Province, between October 1, 2008 and March 31, 2009. HIV-positive spouses were interviewed by local health professionals. Quality of life was evaluated by WHOQOL (Chinese Version). A multiple linear regression model was used to analyze the related factors.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
22
5
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
10
22
5
6
Order By: Relevance
“…2 However, a study done in Estonia had most of their respondents less than age 30 years; 16 while another study conducted in Henan Province got a higher mean age. 17 In contrary, the mean age in this study was found to be 36.49 years (±13.77), however was similar to other studies. (18)(19)(20)(21) Similar to this study, there is a higher male preponderance in the diseased state as reported in a study done among people with HIV/TB co-infection as well as those fielded in WHO global tuberculosis report.…”
Section: Socio-demographic Profile Of Participantssupporting
confidence: 80%
“…2 However, a study done in Estonia had most of their respondents less than age 30 years; 16 while another study conducted in Henan Province got a higher mean age. 17 In contrary, the mean age in this study was found to be 36.49 years (±13.77), however was similar to other studies. (18)(19)(20)(21) Similar to this study, there is a higher male preponderance in the diseased state as reported in a study done among people with HIV/TB co-infection as well as those fielded in WHO global tuberculosis report.…”
Section: Socio-demographic Profile Of Participantssupporting
confidence: 80%
“…According to Shan et al [22], among medical history variables, HIV-infected persons with worse health conditions are inclined to have worse QoL. One of the most acknowledged clinical variables associated with QoL of PLHIV is the breakdown of immunity which is the main cause of symptoms in HIV and is associated with lower QoL [20, 22].…”
Section: Discussionmentioning
confidence: 99%
“…33 The education level was low (1.78% with education !10 years) and female PLWHA made up the majority of previous cases (56.39% female). By contrast, among our study population, 89.5% of PLWHA were men and 43.8% of the participants were gay.…”
Section: Discussionmentioning
confidence: 99%